Development and validation of Emotional Labour in Nursing Scale in Italy - Badolamenti, Sondra; Biagioli, Valentina; Zaghini, Francesco; Caruso, Rosario; Sili, Alessandro (La Medicina del Lavoro, 2018)
Background: Emotional demands may be a significant risk factor for wellbeing in healthcare professionals. Nurses have been considered the most exposed to emotional burden known as emotional labour. Scholars define it as the process by which nurses sometimes hide/fake the real emotion or struggle to display the appropriate emotion to meet the emotional work requirements. Emotional labour can result in physical, psychological and behavioural disorders. A specific tool to measure it among nurses is still missing. Objectives: This study aims to develop and validate an emotional labour scale for nurses. Methods: The design process consisted of three different phases. In the first one, 24 items have been selected from different tools. The second consisted of the assessment of the face and content validity. In the third phase, the Emotional labour scale has been psychometrically evaluated through a cross validation approach, including both exploratory factor analysis performed on a sample of 205 Italian nurses, with the final selection of an 11- items tool, and confirmatory factor analysis.Results: Emotional labour is acted through surface acting, compliance and restraint. The Emotional Labour Nursing scale showed good psychometric properties and was found to be valid and reliable for assessing emotional labour among nurses. The association between emotional labour and burnout was investigated. Conclusions: The Emotional Labour scale may foster a fuller understanding of the consequences of emotional labour. Since emotional demands and emotional labour are not included in the most common psychosocial risk assessment tools currently available, our results point out to their role in work stress prevention.